Właściwość trybunałów kościelnych w sprawach małżeńskich w okresie od 1917 do 1983 roku - Janczewski, Zbigniew (Prawo Kanoniczne, 1995)
This article would like to show the changes in matrimonial processes in competent forum. The first part is about definition and kinds of competent forum, next part is about competent of second and next instance in the Roman Catholic Church and in the Church in Poland. Third part of article shows other problems concern the competent forum: contemporary competent forum of the Church and state, it is not legally competent of tribunal and transfer of the issue.